Guidelines for consequence analysis of chemical releases. (American Institute of Chemical Engineers, 1999)
This Guidelines book provides technical information on how to conduct a consequence analysis to satisfy your company's needs and the EPA rules. It covers quantifying the size of a release, dispersion of vapor clouds to an endpoint concentration, outcomes for various types of explosions and fires, and the effect of the release on people and structures. Special Details: Includes CD-ROM with example problems worked using Excel and Quattro Pro. For use with Windows 95, 98, and NT.
Keywords: Chemical plants -- Accidents -- Evaluation.; Risk assessment.; elektronické knihy; electronic books